2020
DOI: 10.2147/cia.s258381
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of IL-6 and hsCRP Serum Levels on Functional Prognosis in Stroke Patients Undergoing IV-Thrombolysis: Retrospective Analysis</p>

Abstract: Purpose We evaluated the relationship between pretreatment IL-6 and hsCRP levels, symptom severity and functional outcome of patients with acute ischemic stroke (AIS) treated with IV-thrombolysis. Patients and Methods IL-6 and hsCRP samples were obtained from 83 consecutively treated Caucasian patients with AIS prior to initiation of IV-thrombolysis. Severity of stroke symptoms was assessed using the National Institutes of Health Stroke Scale (NIHSS), whereas functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Several previous studies have reported associations between IL‐6 and stroke recurrence 12–15 as well as associations between IL‐6 and functional disability independent of conventional risk factors among ischemic stroke patients 16–18 . Results from Mendelian randomization analyses provided evidence for a causal effect of IL‐6 signaling on ischemic stroke as well 29,30 .…”
Section: Discussionmentioning
confidence: 83%
“…Several previous studies have reported associations between IL‐6 and stroke recurrence 12–15 as well as associations between IL‐6 and functional disability independent of conventional risk factors among ischemic stroke patients 16–18 . Results from Mendelian randomization analyses provided evidence for a causal effect of IL‐6 signaling on ischemic stroke as well 29,30 .…”
Section: Discussionmentioning
confidence: 83%
“…Anti-TNFα treatment signi cantly improves endothelial cell necrosis, attenuates disruption of the blood-brain barrier, and improves stroke outcome (Chen et al 2019). IL-6 is a pleiotropic cytokine that can be identi ed within 12-72 h of acute stroke onset and is a marker of in ammation in acute ischemic brain injury (Pawluk et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[17] Studies have also associated these in ammatory markers with increased mortality, recurrent vascular risk, and poor functional outcome. [15] They have been suggested to cause injury to vascular endothelial cells, promote the release of in ammatory factors, and activate the coagulation cascade that can lead to further expansion of the infarct core after stroke. [3,[20][21][22][23] The most studied in ammatory cytokines in AIS are the pro-in ammatory cytokines IL-1β, Il-6, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown a signi cant increase in IL-6 concentration in the serum within a few hours of onset of ischemia, which lasts for up to 90 days after stroke. [11] Pawluk et al [15] suggested that IL-6 has potential prognostic signi cance for the success of thrombolytic therapy.…”
Section: Introductionmentioning
confidence: 99%